تأثير صفة حرف "الراء" على معاني الكلمات في القرآن الكريم - Malia Fransisca (AN-NAS, 2019)
“One of the characteristics of the ro’ is evidence which means it was vibrating or moving. I mean, when ro’ said, then the tongue we will vibrate. So in the law tajwid be explained that ro’ is divided into two ro’ tafkhim and tarqiq. Ro’ tafkhim the ro’ to read thick. Example: الرَّحْمَنُ، الرَّحِيْمُ. Ro’ tarqiq the ro’ those thin. Example: وَطُوْرِ سِيْنِيْنَ. That’s according to the terms of the identifying of it. Now, we are trying go analysis in terms of its meaning. Is there a connection between the identifying of the ro’ the vibrating with the exact meaning of the word in the Quran that used the ro’? يَنْظُرُ means to see. In the process of looking there must be moving, whether it was his heart or eyes itself. Heart of the visionary vibrate could be due to see something scary such as: accident or ghost. There are times when see something beautiful such as: mountains, garden etc. Or eyes itself moving to the right-left seeing things one ago other object that is in the next to side. يَخْرُجُ means that out. In the process out, there is definitely a part of the body moving the feet. For example want out class but if not move his feet then the main purpose to get out class not reached. Besides limbs, there objects two nearby move when we came out class as bench, tile, earth although the movement no visible to the invisible because of lack of the power of the beat of the foot of the human. And there are many more fi’il (verb) which are referred to in the synchronous Quran between the nature of letters and the meaning of the words.”